Fear of cancer recurrence, supportive care needs, and the utilization of psychosocial services in cancer survivors: A cross‐sectional survey in Hong Kong. Issue 4 (16th December 2020) - Li, Man Chung; Cheng, Hui Lin
Abstract: Objective: Fear of cancer recurrence (FCR) is the top‐ranked psychological concern in cancer survivors. We examined the prevalence of FCR and the relationships among FCR, supportive care needs, and the utilization of psychosocial services among Chinese cancer survivors. Methods: This cross‐sectional, correlational study included 311 cancer survivors within 5 years of survivorship in Hong Kong. The participants were invited to complete an online survey: the Fear of Progression Questionnaire‐Short Form to assess FCR; the 34‐item Supportive Care Needs‐Short Form to assess supportive care needs, and a self‐constructed questionnaire to assess psychosocial services utilization. A score of ≥34 indicated FCR. Descriptive statistics and hierarchical regression analyses were performed. Results: Of the participants surveyed, 38.3% were classified as having FCR. The most frequently reported supportive care needs in five domains were in the psychological domain ( M = 39.5; SD = 27.6), followed by the health system and information domain ( M = 38.6, SD = 26.9). Of the three categories of psychosocial services, informational/educational healthcare services were the most frequently utilized (81%), while the least utilized services were mental health/psychological well‐being support (46.9%). FCR was a consistent factor that was associated with needs in five domains ( b = 8.73–39.58, all p < 0.001). However, FCR was not associated with any of the three categories of psychosocial services utilization. Conclusion: FCR is frequent in cancer survivors. FCR may play an important role in supportive care needs, but not in psychosocial services utilization. There is an increasing demand to bridge the service gap between the need for and the use of mental health and psychological well‐being services.